A problem for degenerated semilinear hyperbolic system in sector - Andrusyak, R.V.; Kyrylych, V.M.; Peliushkevych, О.V. (Carpathian Mathematical Publications, 2011)
A boundary problem for the semilinear hyperbolic system in a sector is considered. Some equations of the system have horizontal characteristics. Applying the method of characteristics and princeple of contractive mappings the conditions for global generalized solvability of the problem are established.